Spatial and spatiotemporal clustering of the COVID-19 pandemic in Ecuador - Patricia Ballesteros; Emily Salazar; Diana Sánchez; Carlos Bolanos (Revista de la Facultad de Medicina, 2021)
Introduction: In Ecuador, the first COVID-19 case, the disease caused by the SARS-CoV-2 virus, was officially reported on February 29, 2020. As of April 2, the officially confirmed numbers of COVID-19 cases and deaths from it were 3 163 and 120, respectively, that is, a mortality rate of 3.8%.